Lightweight Nanofibrous Crosslinked Composite Aerogels with Controllable Shapes and Superelasticity for Pressure Sensors. Issue 7 (12th January 2022) - Ouyang, Zhaofeng; Wang, Chuang; Xu, Dewen; Yu, Hou‐Yong; Zhou, Ying; Mu, Mengya; Ge, Dan; Miao, Zhouyu; Tam, Kam Chiu
Abstract: So far it is still a big challenge to construct the nanofibrous crosslinked composite aerogels with high compressive stress and excellent elastic resilience for pressure sensors. To solve this problem, a novel strategy of combining rigid inorganic nanofibers and flexible organic nanofibers is designed to obtain the crosslinked composite aerogels with outstanding compressive stress and stability. Surprisingly, the as‐prepared composite aerogels have an extremely low density of 11.27 mg cm −3, and the crosslinked composite aerogels with desire shapes can be easily controlled via changing the different molds on demand. More importantly, the composite aerogels can be compressed up to 80% with a quite high compressive stress of 41 kPa and it can recover to its original state well. It is worth mentioning that the as‐prepared aerogels can be encapsulated to construct ultrasensitive (0.53 kPa −1 ) and rapidly responsive (315 ms) pressure sensors for encrypted information transmission. Such excellent crosslinked composite aerogels will open up numerous application opportunities for pressure sensors, thermal insulation, and sound absorption. Abstract : The lightweight nanofibrous composite aerogels with desire shapes and low density of 11.27 mg cm −3 are constructed successfully, which can be compressed up to 80% at 41 kPa and it can recover to its original state well. The composite aerogels can be integrated to pressure sensors with excellent sensitivity (0.53 kPa −1 ) and rapid response (315 ms) for encrypted information transmission.